Pulmonic Stenosis-Ventricular Septal Defect (Teratology of Fallot) Origin and Treatment - M. Ali, Ban; M.S. Ibrahim, Orooba; Z.Yahya, Nibras (Journal of Neonatal Surgery, 2025)
Tetralogy of Fallot (TOF) is the most prevalent form of cyanotic congenital heart disease, comprising four distinct anatomical defects with varying degrees of severity. The clinical presentation in neonates largely depends on the extent of right ventricular outflow tract (RVOT) obstruction and the patency of the ductus arteriosus. Common symptoms include irritability, excessive sweating, cyanotic spells, and heart failure. Accurate diagnosis requires a combination of imaging techniques such as prenatal sonography, Doppler echocardiography, cardiac catheterization, multi-detector CT (MDCT), and MRI, all of which provide insights into the complex physiological abnormalities associated with TOF